VUV sensitisation of Eu3+ emission by Tb3+ in Ba3Tb(PO4)(3)-Eu - Mikhailik, V; Kraus, H (2009)
The luminescence properties of Ba3Tb0.9Eu0.1(PO4)3 and Ba3Gd0.9Eu0.1(PO4)3 phosphors were studied for excitation over the 120-300 nm wavelength range. It is found that Tb3+, which exhibits a strong vacuum-ultraviolet (VUV) absorption band, provides sensitisation of Eu3+ emission in this host. This effect can be used to develop phosphors with enhanced conversion efficiency of the VUV radiation into visible light. © 2009 Elsevier B.V. All rights reserved.